The Nalco water handbook. - Flynn, Daniel J., ....- (New York : McGraw-Hill, 2009)
Developed by the world's leading integrated water treatment and process improvement company, The Nalco Water Handbook, Third Edition provides comprehensive guidance on the use and conditioning of water and wastewater in any industrial or institutional facility. Reflecting major advances in technology and the latest regulatory requirements, this thoroughly revised classic covers basic water chemistry and explains how to improve water quality, minimize water usage, and implement more efficient treatment processes. The Third Edition features new information on wastewater, cooling systems, microbiological control, energy conservation, environmental hygiene, and steam generation problems and prevention. Every essential water treatment topic is covered in this authoritative volume, including: The chemistry of water Water sources Contaminants Impurity removal Steam generation Energy in water systems Wastewater discharge Industrial and municipal use of water